Une femme faussaire dans les Landes de Gascogne sous l’Ancien-Régime - Bernard Traimond (Criminocorpus)
The Gascon folkloriste Félix Arnaudin (1844-1921) tells the story of the lady of Z, model of the woman counterfeiter who would have lived and made of the counterfeit money at the beginning of the XVIIIth century to Escource. It is the part of the imagination in the preparation of narratives on the woman counterfeiter who is studied here according to the model of the “stories of family” eventually understand the construction of the literary figure of the woman counterfeiter of Landes.